Once-weekly subcutaneous semaglutide use I GLP-1 naïve patients with type 2 diabetes in North Macedonia: real world data from the MIRAGE study. - Milenkovikj, Tatjana; Jovanovska Mishevska, Sasha; Bitoska Mileva, Iskra; Ahmeti, Irfan; Chekorova Mitreva, Biljana (My University, 2023)
Safety and efficacy of once weekly (OW) subcutaneous (s.c.) semaglutide in T2D patients has been established in phase 3 clinical trials. In North Macedonia, no real-world evidence studies were conducted so far to assess the use of once weekly (OW) semaglutide in routine clinical practice.